Knowledge and Experiences of Health Professionals in the Peripheral Management of Leishmaniasis in Morocco (ELHajeb) - K. El-Mouhdi; M. Fekhaoui; F. Elhamdaoui; H. Guessioui; A. Chahlaoui (Journal of Parasitology Research)
Background. Morocco hopes to eliminate leishmaniases by 2030. These diseases exist in cutaneous and visceral forms and constitute a serious public health problem. The fight against these parasitoses is carried out within the framework of a national program to control leishmaniases, which offers free treatment. However, the screening rate in public health structures does not exceed 35%. Objective. To determine the knowledge and experience of the social actors directly involved in the fight against leishmaniasis to contribute to analyse and understand the factors of this underreporting and to draw scientific recommendations to improve screening and control activities. Methods. Using a self-administered questionnaire, we conducted an exploratory survey during April and May 2019 among all health professionals working in public health structures in the province of ELHajeb in central Morocco. Results. We found that most of the health professionals had good knowledge about the clinical signs of each form of leishmaniasis, but they had erroneous information about the true vector of the disease, the reservoirs, and the mode of transmission. 76% recognized the national leishmaniases control program and only 17% received continuing education. 85% of these professionals focused on the curative aspects of the program. 47% stated that patients do not adhere to the antileishmaniasis treatment, and 25% stated that the population uses the concept of “Hboub of Chniwla” to refer to cutaneous leishmaniasis. Conclusion. The study concluded that the operationalization of the activities of the leishmaniases control program recognizes some weaknesses which explain the underscreening of cases. Improvement of this situation requires the implementation of continuous training programs for caregivers and awareness-raising programs for citizens which should focus on the mode of transmission, preventive measures against reservoirs, sand flies bites, and recognition of lesions using the popular names of the disease as a starting point.